2019
DOI: 10.1103/physrevmaterials.3.074602
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a second-order Peierls-driven metal-insulator transition in crystalline NbO2

Abstract: The metal-insulator transition of NbO2 is thought to be important for the functioning of recent niobium oxide-based memristor devices, and is often described as a Mott transition in these contexts. However, the actual transition mechanism remains unclear, as current devices actually employ electroformed NbOx that may be inherently different to crystalline NbO2. We report on our synchrotron x-ray spectroscopy and density functional theory study of crystalline, epitaxial NbO2 thin films grown by Pulsed Laser Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
4
23
1
Order By: Relevance
“…Material quality issues and the high transition temperature have limited experimental studies, but our recent hightemperature hard X-ray photoelectron spectroscopy (HAXPES) of crystalline NbO 2 confirmed the predictions of a structurally driven MIT described in terms of a second-order Peierls transition. 10 The onset of metallicity coincides with the gradual symmetrization of the Nb−Nb dimers whereby a structural phase transition (SPT) from the body-centered tetragonal structure (BCT) to the rutile structure (R) occurs. The NbO 2 electronic transition takes place over a large temperature window before reaching the rutile phase.…”
Section: ■ Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Material quality issues and the high transition temperature have limited experimental studies, but our recent hightemperature hard X-ray photoelectron spectroscopy (HAXPES) of crystalline NbO 2 confirmed the predictions of a structurally driven MIT described in terms of a second-order Peierls transition. 10 The onset of metallicity coincides with the gradual symmetrization of the Nb−Nb dimers whereby a structural phase transition (SPT) from the body-centered tetragonal structure (BCT) to the rutile structure (R) occurs. The NbO 2 electronic transition takes place over a large temperature window before reaching the rutile phase.…”
Section: ■ Introductionmentioning
confidence: 86%
“…Preliminary studies of NbO 2 revealed an oxidized surface even under extremely reducing conditions, i.e., >1000 K in ultrahigh vacuum. 10 There have been numerous studies devoted to determining the switching mechanism of adaptive oxides, such as vanadium and niobium oxides, using surface-based experimental methods to infer bulk phase transitions. 13−16 The difference in the ionic arrangements between the bulk and the surface would explain reports of decoupled transition in other Peierls systems, such as VO 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…[8][9][10] A dimerization of the Nb-Nb d-orbitals along the [001]direction in distorted rutile leads to the formation of a band gap. 11,12 In this direction, the strongest change in resistivity due to the metal-insulator transition can be observed , making this crystal orientation interesting for device applications. 5,[13][14][15] For lateral resistive switching devices, NbO2 layers with an in-plane [001] direction have been demonstrated.…”
mentioning
confidence: 99%
“…In fact, only a small increase of around 0.07 Å in the Nb-Nb bond could already prevent the formation of a band gap. 12 In this case, two current paths act in parallel: One along conductive (metallic) grain boundaries, the other one through the semiconducting grains. This explains the large difference of resistivity between the as-grown samples with small grains and the annealed ones with large grains and thus less conductive grain boundaries.…”
mentioning
confidence: 99%
“…From a fundamental viewpoint, the correlation effects of 3d orbitals in transition metal oxides exhibit rich ground state properties ranging all the way from metallic ferromagnets to wide-gap semi-conductors [10,11]. For instance, the MIT in VO 2 is near room temperature, but the isoelectronic compound, NbO 2 , has a transition temperature orders of magnitude higher [12,13], and TiO 2 lacks a transition entirely [14]. The origin of the MIT in VO 2 remains contested [15] after years of study because neither a Peierls [10,16,17] nor a Mott picture align entirely with all the experimental evidence [18][19][20][21][22][23][24].…”
Section: Introduction -mentioning
confidence: 99%